2011
DOI: 10.1371/journal.pone.0022931
|View full text |Cite
|
Sign up to set email alerts
|

Rab18 Dynamics in Adipocytes in Relation to Lipogenesis, Lipolysis and Obesity

Abstract: Lipid droplets (LDs) are organelles that coordinate lipid storage and mobilization, both processes being especially important in cells specialized in managing fat, the adipocytes. Proteomic analyses of LDs have consistently identified the small GTPase Rab18 as a component of the LD coat. However, the specific contribution of Rab18 to adipocyte function remains to be elucidated. Herein, we have analyzed Rab18 expression, intracellular localization and function in relation to the metabolic status of adipocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
120
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(139 citation statements)
references
References 65 publications
(88 reference statements)
8
120
0
Order By: Relevance
“…fasting and diet-induced or genetic obesity), and thyroid function. These observations, mostly based on mRNA data, are in agreement with previous functional results supporting the participation of Rab18 in the regulation of lipid metabolism in adipose tissue (Pulido et al 2011). Effects of fasting on WAT Rab18 expression.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…fasting and diet-induced or genetic obesity), and thyroid function. These observations, mostly based on mRNA data, are in agreement with previous functional results supporting the participation of Rab18 in the regulation of lipid metabolism in adipose tissue (Pulido et al 2011). Effects of fasting on WAT Rab18 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with these early studies, we recently demonstrated that RAB18 overexpression increased basal lipolysis and RAB18 silencing-impaired forskolin-stimulated lipolysis in 3T3-L1 cells (Pulido et al 2011). Intriguingly, we also observed that insulin, like the b-adrenergic receptor agonist isoproterenol, induced the recruitment of RAB18 to the surface of LDs in 3T3-L1 cells, where silencing of RAB18 impaired insulin-stimulated lipogenesis and its overexpression enhanced lipogenesis (Pulido et al 2011). Together, these data suggest that RAB18 plays a role in both lipolysis and lipogenesis in 3T3-L1 adipocytes.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations